Neurotoxic Agent-Induced Injury in Neurodegenerative Disease Model: Focus on Involvement of Glutamate Receptors - Jakaria, Md.; Park, Shin-Young; Haque, Md. Ezazul; Karthivashan, Govindarajan; Kim, In-Su; Ganesan, Palanivel; Choi, Dong-Kug (Frontiers in Molecular Neuroscience, 2018)
Glutamate receptors play a crucial role in the central nervous system and are implicated in different brain disorders. They portray a significant role in the pathogenesis of neurodegenerative diseases (NDDs), like Alzheimer’s diseases, Parkinson’s disease, Amyotrophic lateral sclerosis, etc. Although many studies have been done, the exact pathophysiological characteristics of NDDs are not fully understood yet. In the neurotoxic-induced in vivo and in vitro neurodegenerative disease models, neurotoxic agents cause several neuronal injuries that might be helpful to correlate disease pathological characteristics. Moreover, potential therapeutic drugs discovery might be possible based on the study employing these models. Different neurotoxic agents, namely, kainic acid, domoic acid, glutamate, amyloid beta, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, 1-methyl-4-phenylpyridinium, rotenone and methamphetamine etc. can potently impair both ionotropic and metabotropic glutamate receptors, leading to progression of toxicities in neurodegenerative disease models. Apart from these neurotoxic agents, many neurotoxic agents impair mainly ionotropic glutamate receptors functions. We deliberately express the particular neurotoxic agents that can act glutamate receptors in an effective way to mimic NDD models. Hence, it can be of assistance to co-relate disease characteristics and glutamate receptors targeting drug discovery and development for NDDs.